Forensic psychologists : prisons, power, and vulnerability - Warr, Jason (Emerald Publishing Limited, 2020)
This book explores how forensic psychology has come to inhabit a central unifying discursive presence in the life world of modern carceral institutions. Providing a sociological and qualitative account of forensic practitioner psychologists, the author looks both in, and alongside, the work of such practitioners to explore how they simultaneously occupy positions of power and vulnerability. Focusing not only on how practitioners themselves come to embody a pervasive system of disciplinary expertise, but also on how they experience other forms of penal control, the book offers a novel and complete exploration of forensic psychology, the modern prison, and power. This is an accessible text for prison practitioners, criminological and sociological researchers and forensic psychologists on the nature and reality of forensic psychological practice in the contemporary prisons of England and Wales.